Study on relationship between obesity and menstrual disorders - Sen, Liton Chandra; Annee, Israt Jahan; Akter, Naharina; Fatha, Fawzia; Mali, Sujan Kanti; Debnath, Sourav (Asian Journal of Medical and Biological Research, 2018)
Menstrual disorder is a common fact includes menstrual irregularity, amenorrhea, dysmenorrhea, menorrhagia, oligomenorrhea, polymenorrhea and other related symptoms. Realizing the fact, the present investigation was carried out to determine the prevalence of menstrual disorders among female overweight and obese students and their association with different life style factors. A descriptive cross-sectional study was carried out among 70 overweight students from Patuakhali science and Technology University, Bangladesh through self-administered structural questionnaires. The data were collected on hemoglobin level (g/dl); menstrual pattern viz. menstrual cycle length, duration and flow; lifestyle factors including junk food consumption and dietary pattern. The statistical test was carried out using SPSS V16. The hemoglobin level test ensured that 20% students were non-anemic, 44.3% were mild anemic and 35.7 % were moderate anemic and the mean hemoglobin level was 10.12g/dL. The most commonly observed menstrual disorders among students were dysmenorrhea (47.1%), irregular menstruation (11.4%), menorrhagia (1.4%) and oligomenorrhea (11%). It was observed that 1.4% had scanty flow, 65.7% had normal flow whereas 32.9% had heavy flow of blood. However, the mean flow was 31.6ml. The habit of junk food consumption was found in 88.6% of the respondents and 24.3% of the students practice dieting. Additionally, the respondents who didn’t consume junk foods had regular cycle length although about 88.6% students had regular menstruation cycle and 78.2% had normal duration of flow. Most of the respondents were in moderate dietary diversity score (10.5%) because they maintain a diet chart. The hemoglobin levels ensured that 80% students were found clinically anemic. Thus the study concluded that obesity made the students susceptible to anemia. Asian J. Med. Biol. Res. September 2018, 4(3): 259-266